The Prevalence of Parasites in the Domestic Pigeons (Columba livia domestica) in Zakho City, Kurdistan-Iraq (Baghdad Science Journal, 2021)
Pigeons have accompanied humans since ancient time because they are used as a source of food, pets, hobby, and religious symbols. Pigeons have shown high prevalence rate of infection with gastrointestinal helminths and protozoan. This study was conducted to evaluate the prevalence of parasitic infections in the domestic pigeon (Columba livia domestica) from October, 2017 to April, 2018, purchased from bird market of Zakho City, Kurdistan region. The samples were taken from 50 adult pigeons (28 males and 22 females). The birds were transferred to Parasitology Laboratory, Faculty of Science, Zakho University. In the laboratory, each bird was sacrificed and immediately the feather and skin of under wings, chest and the rest of the body was examined for ectoparasites. The collected ectoparasites were preserved in 70% alcohol for further study. The sacrificed birds were dissected and their intestine and contained were examined for the presence of parasites. The results revealed a total rate of 76% of infection with ectoparasites, which included three species of lice, namely: Columbicola columbae (56%), Companulotes compar (36%) and Hohorstiella lata (10%). Regarding helminths, cestodes were the only helminths found in this study with a rate of 16% (8/50). Three species of cestodes were recorded, they included: Raillietina cesticillus(14%), Raillietina echinobothrida(4%) and Choanotaenia infundibulum (2%). Further studies are required to evaluate the effect of the recovered parasites on this host and their transmission to other poultry flocks and human.Keywords: Pigeon, Ectoparasites, Cestodes, Prevalence.